Tourist carrying cacacity, basis for sustainable management: Huagapo Grotto - Huaroc Ponce, Edwin Jhon (2021)
The cave of Huagapo located in the district of Palcamayo province of Tarma in the Junín region – Peru, at 3572 m.s.n.m. currently said natural training was traveled up to 2800 meters, currently for tourist use from the entrance of the grotto are 212m.(dry route). The research was based on the analysis of tourist load capacity (CCT), with the methodology of Cifuentes 2003, Finding first the physical load capacity (CCF), then analyzed correction factors (Fc) o find the actual load capacity (CCR), it was subsequently analyzed as manageable capacity (CM) and this was multiplied with the CCR. Thus achieving the effective load capacity (CCE) or what is called the tourist load capacity (CCT). The results of which were: CCF 2 692 visits per day; Fc. 0.324002; CCE 872 visitors per day and finally CCE 483 visitors per day. This can be said to be the first phase or task to develop sustainable tourism activity in the n the tourist attraction GRUTA DE HUAGAPO